Retrospektywna analiza wzrokowych potencjałów wywołanych w przypadkach istnienia różnych chorób układowych i chorób oczu - Pojda-Wilczek, Dorota (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
Purpose: Significantly increased latency of VEP assessment in various ocular and systemic disorders and discussion of VEP interpretation problems in patients with sudden loss of visual acuity. Material and methods: A retrospective analysis of pattern VEP in 352 patients with suspected retrobulbar optic neuritis and 892 patients with significantly increased (more than three standard deviations) P100 latency was performed. Transient pattern VEP (PVEP) was recorded in accordance with ISCEV standards with the use of two active electrodes in the occipital region (from left and right sides). Results: The most frequent cause of increased P100 latency was multiple sclerosis. Other conditions associated with delay P100 latency included: macular dystrophies and degenerations, optic neuritis, glaucoma and other optic neuropathies, circulatory problems, chorioretinitis, arterial hypertension, diabetes, ischemic heart disease, chronic renal failure, acute pancreatitis, pediatric problems, and initial cataract. Sudden loss of visual acuity was caused by: retrobulbar optic neuritis (50%), anterior ischemic optic neuropathy, spasm of accommodation, migraine and functional disorders. Conclusions: If VEP results are normal, visual acuity loss is usually functional. A detailed knowledge of all the factors, which may influence VEP, is essential for its correct interpretation.